Cosa è Evidente e cosa è Fondante in Educazione. Alcune riflessioni sull’Evidence-Based Education - d’Agnese, Vasco (Studi sulla Formazione/Open Journal of Education, 2014)
This essay provides a critical examination of Education as an Evidence based practice, focusing on three orders of limits: episthemological, ethical, and pragmatical. First of all the epistemology of Evidence based practice is an old one: we know, from Karl Popper to Thomas Kuhn, from Alexandre Koyré to Michel Foucault, from Wittgenstein to Richard Rorty that the logic of scientific discovery is very complex, involving several orders of factors; when we develop a research we can’t never say : “this is an ultimate evidence”. Of course we must go on and try out conclusions. But the way in which we think education, the social and interactive nature of educational process vented serious doubts about the nature of evidence we must accept. Then, Evidence based practice seems to provide a framework to avoid the personal responsibility in choosing one way or another – that’s why it’s so attractive -. In order to pragmatical limits, we argue that we don’t know the whole educational process from the beginning and working only on a preconceived evidence will restrict the possibilities of education and will not work in order to an expansion of opportunities of people who are involved in educational process.